Tyrosine phosphorylation of components of the B-cell antigen receptors following receptor crosslinking. - Gold, M R (1991)
Crosslinking membrane immunoglobulin (mIg), the B-cell antigen receptor, stimulates tyrosine phosphorylation of a number of proteins. Since many receptors are phosphorylated after ligand binding, we asked if components of the mIg receptor complexes were tyrosine-phosphorylated after mIg crosslinking. Both mIgM and mIgD are noncovalently associated with at least two other proteins. mIgM is associated with the MB-1 protein, which is disulfide-linked to a protein designated Ig-beta. mIgD is not associated with MB-1 but is with IgD-alpha, which is also disulfide-linked to Ig-beta. Using immunoprecipitation with a specific anti-MB-1 antiserum followed by anti-phosphotyrosine immunoblotting, we found that crosslinking mIgM stimulated tyrosine phosphorylation of MB-1, Ig-beta, and a previously unidentified 54-kDa polypeptide associated with MB-1. In mature splenic B cells that express both mIgM and mIgD, mIgM crosslinking stimulated tyrosine phosphorylation of the 32-kDa MB-1 protein, whereas mIgD crosslinking stimulated tyrosine phosphorylation of MB-1-related proteins of 33 and 34 kDa. The 32-kDa MB-1 protein was only associated with mIgM, whereas the 33- and 34-kDa MB-1-related proteins were specifically associated with mIgD and are most likely IgD-alpha. Thus, crosslinking either mIgM or mIgD stimulated tyrosine phosphorylation only of the MB-1-related proteins associated with that receptor.